Співвідношення системи покарань Руської Правди та правових пам'яток Новгородської землі: історико-правове дослідження - Коваль, Т.Ф. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
This article depicts the correlations between the characters of the Russian Pravda punishment system and the system of Novgorodska republic law memorials. It was proved that the Russian Pravda punishment system had been reflected in the law memorials of Novgorodregion. It was established that the common features of the punishment system were fines and enhancing of woman right protection and tortures were not applied.